PENGARUH LIVE COMMERCE DAN KETERLIBATAN KONSUMEN TERHADAP PEMBELIAN IMPULSIF PADA SANDALSELOP.ID DI TIKTOK - Siti Saripatul Mawadah; Muhammad Musyfiq Salami (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This study aims to analyze the influence of Live commerce and Consumer Involvement on Impulsive Purchases on sandalselop.id on TikTok. The rapidly growing Live commerce phenomenon on TikTok opens up new opportunities for business actors in encouraging spontaneous purchasing decisions. This study uses a quantitative approach by distributing questionnaires to 100 respondents who have participated in Live commerce. Data analysis techniques include validity tests, reliability tests, classical assumptions, linear regression, correlation coefficients, determination coefficients, t-tests, and f-tests, with the help of SPSS version 20. The results show that both Live commerce and Consumer Involvement have a partial significant effect on Impulsive Purchases with a significance value of 0.000 (<0.05) each. Simultaneously, both variables also have a significant effect with an Fcount value of 9.629> Ftable 3.09 and a significance of 0.000. The coefficient of determination value of 0.166 indicates that 16.6% of the variation in Impulsive Purchases can be explained by these two variables. This study demonstrates that interactive Live activities and active consumer engagement can drive unplanned purchases. These results can be important considerations for businesses developing digital marketing strategies, particularly through TikTok.